2017
DOI: 10.3389/fpls.2017.00474
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Technologies for Assessing Seed Germination and Trifloxysulfuron-methyl Response in Amaranthus palmeri (Palmer Amaranth)

Abstract: Weed infestations in agricultural systems constitute a serious challenge to agricultural sustainability and food security worldwide. Amaranthus palmeri S. Watson (Palmer amaranth) is one of the most noxious weeds causing significant yield reductions in various crops. The ability to estimate seed viability and herbicide susceptibility is a key factor in the development of a long-term management strategy, particularly since the misuse of herbicides is driving the evolution of herbicide response in various weed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 60 publications
(66 reference statements)
2
22
0
1
Order By: Relevance
“…In this regard, the current study is similar to studies of reflectance-based studies of seed viability [25, 26], ontogeny of blowfly pupae [22], and terminal stress response in insects exposed to killing agents [24]. In addition, we showed how important factors may influence the quality of proximal remote sensing data and that 70% ethanol appears to be the most suitable killing method and solvent for preservation over time of killed specimens.…”
Section: Discussionsupporting
confidence: 78%
“…In this regard, the current study is similar to studies of reflectance-based studies of seed viability [25, 26], ontogeny of blowfly pupae [22], and terminal stress response in insects exposed to killing agents [24]. In addition, we showed how important factors may influence the quality of proximal remote sensing data and that 70% ethanol appears to be the most suitable killing method and solvent for preservation over time of killed specimens.…”
Section: Discussionsupporting
confidence: 78%
“…[16][17][18] While we cannot directly compare the results because we studied kochia and they studied Palmer Amaranth, Italian ryegrass, and general weed identification, respectively, all of these studies suggest promise for using hyperspectral imaging in sitespecific weed management. In particular, previous studies showed 91% classification accuracy for Palmer amaranth 16 and an 80% classification accuracy for Italian ryegrass.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] While we cannot directly compare the results because we studied kochia and they studied Palmer Amaranth, Italian ryegrass, and general weed identification, respectively, all of these studies suggest promise for using hyperspectral imaging in sitespecific weed management. In particular, previous studies showed 91% classification accuracy for Palmer amaranth 16 and an 80% classification accuracy for Italian ryegrass. 17 While our accuracies are lower than those for the Italian ryegrass and for the Palmer amaranth classifications, the results indicate that hyperspectral imaging can be used to identify kochia biotypes, both in the greenhouse and in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process involves a detailed spectral analysis of different weeds (e.g., kochia, marestail, and common lambsquarters) in different crops (e.g., wheat, barley, and sugar beet), aimed at differentiating between herbicide-resistant and -susceptible biotypes of the weed. Other work in this field includes distinguishing between susceptible-and glyphosate-resistant Palmer amaranth biotypes, 14 differentiating between glyphosate-susceptible and glyphosate-resistant Italian ryegrass, 15 and detecting the injury on crops as a result of dicamba and glyphosate. 16 The paper follows this format: Sec.…”
Section: Introductionmentioning
confidence: 99%